2000
DOI: 10.1128/jvi.74.10.4621-4633.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Key Target Sequence To Block Human Immunodeficiency Virus Type 1 Replication within the gag-pol Transframe Domain

Abstract: Although the full sequence of the human immunodeficiency virus type 1 (HIV-1) genome has been known for more than a decade, effective genetic antivirals have yet to be developed. Here we show that, of 22 regions examined, one highly conserved sequence (ACTCTTTGGCAACGA) near the 3 end of the HIV-1 gag-pol transframe region, encoding viral protease residues 4 to 8 and a C-terminal Vpr-binding motif of p6Gag protein in two different reading frames, can be successfully targeted by an antisense peptide nucleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 158 publications
(108 reference statements)
0
19
0
Order By: Relevance
“…8). This is the first report (58) have demonstrated that PNA targeted to the Gag-Pol transframe domain can arrest virus production. However, very high concentrations of PNA (100 M) were required to achieve this effect.…”
Section: Discussionmentioning
confidence: 99%
“…8). This is the first report (58) have demonstrated that PNA targeted to the Gag-Pol transframe domain can arrest virus production. However, very high concentrations of PNA (100 M) were required to achieve this effect.…”
Section: Discussionmentioning
confidence: 99%
“…HIV has been a frequent target for both RNAdegrading and steric-block approaches (Arzumanov et al, 2001b;Boulme et al, 1998;Darfeuille et al, 2002a;Darfeuille et al, 2004;Hiratou et al, 2001;Ittig et al, 2004;Kaushik et al, 2002;Park et al, 2000;Sei et al, 2000;Suzuki et al, 2002;Yamaguchi et al, 1997). For antisense technologies to become drug candidates, sequence specificity is essential.…”
Section: ©2006 International Medical Press 0956-3202mentioning
confidence: 99%
“…Subconfluent COS-7 cells were transfected with 2 g of the pNL4-3 or APP/SPT clones in six-well plates. Efficiency of particle release was determined by measurement of HIV-1 p24 antigen enzyme-linked immunosorbent assay (ELISA) (Abbott, North Chicago, Ill.) in supernatant at 7,9,19,24,30,41, and 45 h posttransfection.…”
Section: Analysis Of P1-p6mentioning
confidence: 99%